Near‐shore geophysical and geotechnical investigations in support of the Trieste Marine Terminal extension. Issue 1 (20th January 2020) - Masoli, Carlo Alberto; Petronio, Lorenzo; Gordini, Emiliano; Deponte, Michele; Boehm, Gualtiero; Cotterle, Diego; Romeo, Roberto; Barbagallo, Alfio; Belletti, Rinaldo; Maffione, Stefano; Meneghini, Fabio; Baradello, Luca
ABSTRACT: The Port of Trieste is an international hub for land and sea trade with the dynamic markets of central and eastern Europe. Thanks to its deep natural draft (about 18 m), the modern high‐capacity vessels can moor to the piers. In view of the foreseen increase in maritime traffic, this harbour is undergoing modernization in order to improve the commercial traffic capability. In this expansion plan, the container Trieste Marine Terminal, Pier VII, is seeking an extension by about 200 m. In support of this feasibility study, multidisciplinary data acquisition was conducted in order to characterize the seabed, the sub‐bottom sediments and the bedrock (flysch formation) in front of the Trieste Marine Terminal. The acquisition of high‐resolution swath bathymetry, side‐scan sonar and magnetometer data allowed a detailed analysis of the seabed conditions from an environmental and safety perspective. High‐resolution seismic reflection data enabled us to characterize the Plio‐Quaternary soft sediments and the underlying bedrock. A static underwater refraction survey was performed using hydrophone array deployed on the sea bottom to obtain seismic velocities and to achieve a reliable time‐to‐depth conversion of reflection seismic data by first‐arrival tomographic inversion. In addition to geophysical investigations, 11 offshore boreholes were drilled for detailed logging. In situ standard penetration tests were performed on core samples with the use of a pocket penetrometer and pocket vane in order to obtain uniaxial compressive strength, undrained shear strength and undrained cohesion values, and assess the cohesive soils. During drilling, 17 undisturbed samples and 12 semi‐disturbed samples were extracted to perform laboratory tests for the identification of the principal geotechnical parameters. The goal was to obtain a reliable geological/geotechnical model in front of the Trieste Marine Terminal – from the seabed to the bedrock. Below the seafloor, a sequence of about 20–30 m thickness, containing Plio‐Quaternary soft sediments, overlies the flysch, which locally presents alteration with rocks of reduced quality. The geophysical–geotechnical integrated approach allowed us to identify and map the top of the bedrock and provided valuable information for planning the pier extension project.